PERSEPSI DAN MOTIVASI DIGITAL NOMAD BERWISATA DI DESA TIBUBENENG, CANGGU, KUTA UTARA - Mulyana, Cipta; Sudana, I Putu; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020)DO - 10.24843/IPTA.2020.v08.i02.p03, 2020)
Bali as an international tourism destination has many tourist attractions, one of which is Canggu. In 2018 nomadlist.com released that Canggu was chosen as the best destination for digital nomads. A new tourist trend has emerged where tourists who work outside the office and complete their work using electronic media such as laptops and internet connections in a coworking space and conduct tourism activities called digital nomads. This research was conducted to determine the Perceptions and Motivations of Digital Nomad travelling in Tibubeneng Village, Canggu village, Badung Regency, Bali. This research was conducted by using questionnaires to digital nomad in several coworking spaces in Tibubeneng Village, Canggu, in addition to distributing questionnaires to the nomads conducted open observation and interviews with several nomads and coworking space staff to complete the data.The results showed that the majority of digital nomads visiting Tibubeneng Village,  Canggu were from Australia and Europe, most of whom worked as entrepreneurs. The indicator on the perception that gets the highest score is hospitality from the digital nomad while the indicator that gets the lowest response is the road conditions to Tibubeneng Village, Canggu. On the motivation indicator, physical motivation gets the highest score from a digital nomad while the motivation with the lowest score is showing prestige.